Manipulability constraint locus for a six degrees of freedom redundant planar manipulator - Yahya, S.; Moghavvemi, M.; Mohamed, H.A.F. (2012)
This paper uses the manipulability constraint locus to evaluate the properties of manipulability measure for singularity avoidance in a six degrees of freedom three dimensional planar redundant manipulator. A manipulability constraint locus is the set of configurations satisfying the optimality constraint for the manipulability measure. Because the manipulability constraint measure requires a heavy computational efforts so that all the previous papers were dealt with the three degrees of freedom two dimensional planar manipulator. In this paper-through a numerical example-the manipulability constraint measure has been obtained for a six degrees of freedom three dimensional planar redundant manipulator.